Competitiveness of health resort enterprise - looking for methods of evaluating cross-border competitiveness of health resort enterprises - Stankiewicz, Boguslaw
Konkurencieschopnosť v turizme, jeho povaha, faktory a modely. Modely hodnotenia podnikov kúpeľnej starostivosti.